2021
DOI: 10.3889/oamjms.2021.7417
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and Determinant of Contraceptive Use among Women in Indonesia from 2007 to 2017: Evidence from Demographic and Health Survey

Abstract: Background: Modern contraceptives are proven as the most effective birth control methods. However, it was a change in the pattern of modern method use in Indonesia to traditional. Objectives: This study investigated the pattern of contraceptive use and its determinant in Indonesia between 2007 and 2017. Methods: The study employed data from the Indonesian Demographic and Health Survey (IDHS) 2007, 2012, and 2017. Eligible participants included all women aged 15–49 who were married/living together with a partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The pattern of association between participants education and participation in FPP show that the higher the level of education, the lower the odds of FPP participation. This finding is similar with previous study [14]. However, this result still in lined and agreed that education had contribution in women's empowerment and decision making in FPP [3], [5], [11].…”
Section: Logistic Regression Models Of Participation In Family Planni...supporting
confidence: 92%
“…The pattern of association between participants education and participation in FPP show that the higher the level of education, the lower the odds of FPP participation. This finding is similar with previous study [14]. However, this result still in lined and agreed that education had contribution in women's empowerment and decision making in FPP [3], [5], [11].…”
Section: Logistic Regression Models Of Participation In Family Planni...supporting
confidence: 92%
“…10 Many studies on contraception conducted using data on a national or provincial scale showed relatively moderate contraceptive use. 4,[14][15][16] Those studies employed data from the Demographic and Health Survey (DHS), Program Performance and Accountability Survey (SKAP), and Inter-Census Population Survey (SUPAS) data. However, studies on contraception in Papua are still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…National Population and FP Board is responsible for demand creation of FP services while Ministry of Health is responsible for its supply. So far, several studies have described the success of FP Program only seen from the public's point of view [2], [3], [4], [5], [6], [7], [8] and the roles of healthcare staff, especially in terms of supply/contraceptive tool supply. Those studies included contraceptive guideline [9], contraceptive financing policies [10], contraceptive usage failure policies [11], education and training for healthcare staff in administering contraceptive services [12], and monitoring and evaluation of FP program for healthcare staff [13].…”
Section: Introductionmentioning
confidence: 99%